Active metabolites of acenocoumarol: do they contribute to the therapeutic effect? - Thijssen, H H (1983)
The pharmacokinetics and pharmacodynamics of racemic acenocoumarol (AC), the amino (AM) and acetamido (AA) derivative were investigated in healthy volunteers after administration of a single oral (10 mg) dose. All three coumarins were rapidly absorbed from the gastrointestinal tract. The elimination half-lives were 10.9, 10.4, and 4.1 h, for AC, AM and AA, respectively. After the oral administration of AC, no AM and AA was detected in the plasma, and less than 1% of the dose was recovered in the urine (0-24 h) as AM. Renal clearance was the main route of elimination of AM and AA; the former by glomerular filtration, the latter by active excretion. Binding to serum proteins was the highest for AC (1.52% free). AM and AA were less tightly bound (about 3% free). AM or AA did not interfere with the AC plasma protein binding. The oral administration of AC resulted in a rise in prothrombin time with a maximum effect at 24 to 30 h. No anticoagulant activity was observed upon the administration of AM and AA. The results indicate that the compounds AM and AA, if they are formed out of AC at all, do not contribute to the anticoagulant activity of AC.